Research on High Speed Stability of Multi-group Autonomous-rail Rapid Tram - ZHONG Hanwen; XIAO Lei; YANG Yong; ZHANG Chenlin; ZHOU Sheng; FU Jianchao; LIU Biao (Kongzhi Yu Xinxi Jishu)
Multi-group autonomous-rail rapid tram has a long body. If it is not controlled in the process of driving, especially in high-speed conditions, it is prone to constant pendulum instability, vertical rollover and other problems, which affect the stability and safety of vehicle. In order to find the change trend of dynamic state quantity of autonomous-rail rapid tram under high speed condition, a whole vehicle dynamics model of three-group autonomous-rail rapid tram is built using the dynamics software Simpack based on vehicle dynamics and control theory. The traction, braking, steering and track following control systems are integrated in Simulink. Through the co-simulation of the integrated control system and the vehicle dynamics model, according to SAE J2179 A test for evaluating the rearward amplification of multi-articulated vehicle, it designs the high speed driving condition of autonomous-rail rapid tram, studies and analyzes the change trend and extremum values of dynamic state variables such as articulation angle, body roll angle, yaw rate and lateral acceleration of each marshalling vehicle at different speeds. Simulation results show that the index values in the dynamic process are small, and the dynamic stability of the whole vehicle is good under the high-speed operation condition.